High extinction‐ratio microstructure fiber based on chalcogenide glasses. Issue 11 (14th June 2021) - Xu, Tiesong; Zhong, Minghui; Liang, Xiaolin; Liu, Jia; Yan, Bin; Xiao, Jing; Jiao, Kai; Wang, Xiange; Si, Nian; Pan, Zhongda; Zhao, Zheming; Wang, Xunsi; et al.
Abstract: Extinction ratio (ER) is one of the important parameters to characterize the polarization‐maintaining (PM) performance of the fiber. In this paper, we report the preparation and properties of a novel chalcogenide microstructure fiber with a high ER. We fabricate a preform using a peeled‐off extrusion method. The core and cladding material of the fiber are Ge9 As23 Se68 and Ge10 As22 Se68 . The preform was drawn into a fiber with an average ER of −17.08 dB. The loss of the fiber is less than 2 dB over 5.20–8.55 μm, and the minimum loss of the fiber is 0.57 dB/m at 6.2 μm. Moreover, a flat mid‐infrared supercontinuum spectrum spanning from 1.53 to 12.50 μm is generated by pumping an 18‐cm‐long PM fiber for the first time.